Pengembangan Bahan Ajar Menulis Teks Cerita Rakyat Berbasis Sosiokultural pada Mata Pelajaran Bahasa Indonesia Kelas X SMA - Anita Lestari Hutagalung, Nila Safina, Rita (Medan Resource Center, 2022)
This study is a type of Research And Development (R&D) that refers to the steps of the research and development model and Gall (1983:772). It was limited from ten steps to five steps that include preliminary studies, product design planning, product development, validation tests by expert lecturers and product revisions. The instrument used in the study was the form of an assessment scale to determine the feasibility of the module and its validity, by using a Likert Scale and arranged in the questionnaire. The data analysis was carried out by collecting qualitative and quantitative data from material experts and design experts. The results of the study on the development of teaching materials for writing sociocultural-based folklore texts indicated that the module product is feasible to be used as learning material. It is based on the assessment score obtained through the assessment score from the material expert 1 is 141 or as 81% with the Very Eligible criteria, the assessment score from the material expert 2 is 132 or as 75% with the Eligible criteria, the assessment score from the design expert 1 is 83 or as 83% with the Very Eligible criteria, and the assessment score from design expert 2 is 100 or as 100% with the Very Eligible criteria. Based on the validaton results of material experts and design experts, it can be concluded that teaching materials for writing folklore texts based on sociocultural are very feasible to be used as teaching materials.